SIMBOL-SIMBOL DALAM TRADISI PERKAWINAN MASYARAKAT BURU DAN IRLANDIA: SUATU ANALISIS SEMIOTIK - Bihuku, Rosalina; Rambing, Rosalina; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACT This research entitled â€œThe Traditional Symbols of Marriage in Buru and Ireland: A Semiotic Analysisâ€. The objectives of this research are to identify, classify, analyze and describe the kinds and meanings of the traditional symbols of marriage in Buru and Ireland and to find out the similarities and the differences of traditional symbols of marriage in Buru and Ireland. This research used a descriptive method. The data of Buru marriage symbols were taken by interviewing four informants who are the native speaker to explain what is unknown by writer, while the data of Irish marriage symbols were taken from several articles. The writer used Peirceâ€Ÿs theory in anylizing the data and Ladoâ€Ÿs theory in contrasting both cultures to find out the differences and similarities. The result of this research shows that the marriage culture in Buru has 6 kinds of symbol such as areca nut as a symbol of agreement, spear and machete as a symbol of proposal, the dowry for the brideâ€Ÿs parents, sign for daughter and son in law as a symbol husband and wife, the dowry for all family of the bride, and gong. Irish marriage culture has 9 kinds of symbol such as claddagh ring as a symbol of love, loyality and friendship, bouquet as a symbol of fertility, blue wedding dress as a symbol of lucky, wedding cake as a symbol of fertility, honeymoon as a symbol of the bride and groom after marriage, magic hanky as a symbol of fertility, make-up bells as a symbol of reminder of the couple wedding vows and also restore the harmony, the lucky horseshoe as a symbol of luck and braided hair as a symbol of feminime power and luck. The similarities of traditional symbols in Buru and Ireland are the kind wedding proposal, wedding ring and giving coin which have the same meaning. The differences of both cultures are Irish traditional merriage has wedding dress, wedding cake, honeymoon, bouquet, make-up bells, lucky horses, magic hanky and braided hair while Buru has not. Buru traditional marriage uses the symbols such as areca nut, spear, machete, dowry and gong, while Irish traditional marriage has not. Key words: Symbols, Marriage, Buru and Ireland, Semiotic Analysis